APPLICATION OF CRISIS MANAGEMENT IN CRISIS MANAGEMENT IN KOSOVO AND METOHIA (Heritage, 2024)
Defining and managing the crisis in Kosovo and Metohija brings with it controversy for many political factors, in the sense that today there is no consensus on the domestic political level (even among the subjects of the international community). There are serious disagreements regarding the classification of the crisis in Kosovo and Metohija, in fact its political, legal and security determination. Due to the resulting political changes and trends, in everyday terminology, many terms, ideological concepts, and even real facts are avoided when talking about the problem of Kosovo and Metohija. This paper is an attempt to contribute to a multidimensional definition of the crisis in Kosovo and Metohija and an adequate response to it.
Keywords: crisis, crisis management, security, politics, Kosovo and Metohija